2022
DOI: 10.1111/jog.15350
|View full text |Cite
|
Sign up to set email alerts
|

Association between gestational abnormal glucose tolerance and maternal‐fetal outcomes

Abstract: Aim: To investigate the relationship between abnormal glucose tolerance during pregnancy and maternalfetal outcomes, after categorizing women into groups with different levels of gestational abnormal glucose tolerance. Methods: A total of 1858 pregnant women who received two-step screening for gestational diabetes mellitus (GDM) at Fooyin University Hospital were categorized into four groups, according to their glucose abnormalities, and their maternal-fetal outcomes were investigated from October 2015 to June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Smaller retrospective cohort studies of pregnant individuals with gestational glucose intolerance also report increased risk of macrosomia and larger birth weight. 14,15,33,34 A meta-analysis including cohorts from a wide time period , with heterogeneity of GDM diagnostic criteria and available outcomes, had results consistent with ours. 35 Although this study showed increased risk of LGA and cesarean deliveries, it did not examine additional rarer birth weight-related adverse perinatal outcome included in our study.…”
Section: Be Valuable In Clinical Decision Making About Perinatal Risksupporting
confidence: 82%
See 1 more Smart Citation
“…Smaller retrospective cohort studies of pregnant individuals with gestational glucose intolerance also report increased risk of macrosomia and larger birth weight. 14,15,33,34 A meta-analysis including cohorts from a wide time period , with heterogeneity of GDM diagnostic criteria and available outcomes, had results consistent with ours. 35 Although this study showed increased risk of LGA and cesarean deliveries, it did not examine additional rarer birth weight-related adverse perinatal outcome included in our study.…”
Section: Be Valuable In Clinical Decision Making About Perinatal Risksupporting
confidence: 82%
“…Previous studies examining the risk of cesarean deliveries in this population are largely consistent with our findings, 15,33,35 but there are some mixed data. 34 We found that the odds of severe perineal lacerations were higher in pregnant individuals with gestational glucose intolerance with one abnormal OGTT value but not in those with GDM; this may be related to lack of glucose-lowering treatment and lack of indicated delivery before 40 weeks of gestation in pregnant individuals with gestational glucose intolerance, leading to greater absolute birth weight, 5,9 because higher birth weight is a known risk factor for perineal trauma. To the best of our knowledge, other studies have not reported a positive association between gestational glucose intolerance and severe perineal lacerations; a previous negative retrospective study was likely underpowered.…”
Section: Be Valuable In Clinical Decision Making About Perinatal Riskmentioning
confidence: 88%
“…Indeed, independently of other known risk factors for GDM, ultrasound-estimated maternal visceral adipose tissue (VAT) thickness in pregnancy is strongly associated with insulin resistance and higher risks of developing GDM [ 2 , 3 , 4 , 5 ]. Along with increased adiposity, GDM can have detrimental health consequences for both the mother and the fetus [ 6 , 7 , 8 , 9 ]. Hence, glycemic control is particularly fundamental in all pregnant individuals (with or without GDM), as continuous associations between maternal glucose levels (below those of GDM diagnosis) and adverse pregnancy outcomes, such as primary cesarean delivery and neonatal hypoglycemia, have been observed [ 10 ].…”
Section: Introductionmentioning
confidence: 99%